2020
DOI: 10.1158/1538-7445.am2020-6411
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 6411: Discovery of covalent ligands to novel E3 ligases enables bispecific degraders with highly differentiated protein degradation across a broad range of targets

Abstract: Introduction: Targeted protein degradation is a novel therapeutic modality that holds great promise. Current bispecific degraders have been mostly built using reversible ligands against two well characterized E3 ligases, CRBN and VHL. Features unique to each particular E3 ligase, such as its tissue expression pattern or its intrinsic catalytic efficiency could ultimately impact the in vivo bioactivity of any bifunctional drug based on it. Therefore, discovering ligands to novel E3s has the potential to enable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Collectively, our analyses suggest specific advantages of covalent PROTACs, the proof of which we expect to translate to improvement of degradation efficacy in vivo and ultimately the clinic. Notably, one of the first reported in vivo POC data has shown that a BRD4 PROTAC, VV-957, covalent at the E3 ligase, outperforms reversible BRD4 PROTACs of CRBN/VHL …”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our analyses suggest specific advantages of covalent PROTACs, the proof of which we expect to translate to improvement of degradation efficacy in vivo and ultimately the clinic. Notably, one of the first reported in vivo POC data has shown that a BRD4 PROTAC, VV-957, covalent at the E3 ligase, outperforms reversible BRD4 PROTACs of CRBN/VHL …”
Section: Discussionmentioning
confidence: 99%
“…Among them, the BRD4 PROTAC, VVD-9547 , shows more potent degradation activity than CRBN- and VHL-based PROTACs (dBET1 and MZ1) both in vitro and in vivo . 138 Although the chemical structures and E3 ligase information have not been disclosed yet, the encouraging in vitro and in vivo data suggest that covalent E3 ligase ligands could prove useful for future PROTAC-based drug design.…”
Section: Protacs With Covalent E3 Ligase Ligandsmentioning
confidence: 99%